Allopurinol: An old drug revitalized for CKD?. Issue 6 (June 2015) - Jarrett, Jennie Broders; Koenig, Marianne
Abstract : N/A: Goicoechea M, Garcia de Vinuesa S, Verdalles U, et al. Allopurinol and progression of CKD and cardiovascular events: long‐term follow‐up of a randomized clinical trial. Am J Kidney Dis . 2015; 65(4):543–549.